MEMBANGUN PENDIDIKAN MADRASAH YANG KOMPETITIF DI ERA GLOBALISASI - Basumi, Firdaus (Analisis: Jurnal Studi Keislaman, 2013)
The quality control of education in Madrasas (islamic schools) can be done through three ways, i. e teacher competency enhancement, school  accreditation, and,  lastly,  students’  achievement  in  the National  Examination.   This  research  was  conducted  to  study the impacts   of school accreditation among the madrasas on the teachers  competency    and  students’  achievement  in    national test. The method used is  so called ex post facto   involving 220 teachers taken from 73 madrasas  existing in 4 provinces namely: Jakarta,  Central  Java, South  Sulawesi  and South  Sumatra.  The study reveals that (1) There is no significant difference   in performance  between  teachers  teaching  in accredited  madrasas and  non  accredited;    (2)  There  is  a   significant  difference  in teacher performance in every level of accreditation; (3) There is a significant  difference between   in the teachers performance   in the accredited “B” madrasa and in the accredited “C” ; (4) There is a significant  difference  in   the  achievement  of the  National Examination   between  students   from  the  accredited   madrasas and non-acredited;  (5) There is no significant  difference  in the results  of National  Examination  in all levels of acreditation  (A, B or C).  Based on these facts, it can be concluded that   school accreditation of the  madrasas  has real impacts  on the  teachers competency  and students’ achievement in  national test.